Perceived Motivational Climate and Stages of Exercise Behavior Change: Mediating Roles of Motivation Within and Beyond Physical Education Class - Wu, Xiaojing; Gai, Xiaosong; Yu, Tianfeng; Yu, Haifeng; Zhang, Yu (Frontiers in Psychology, 2021)
This study examined the relationship between the perceived motivational climate in physical education (PE) classes and stage of exercise behavior change among 322 high school students in northeastern China. Furthermore, the chain-mediating effects of autonomous motivation in PE and five types of motivation (interest, competence, social relatedness, appearance, health) in leisure-time physical activity (PA) were examined. Results showed that autonomous motivation in PE and five types of motivation in leisure-time PA had chain-mediating effects on the relationships between the perceived mastery- and performance-oriented motivational climate and stage of exercise behavior change in the whole sample (controlling for gender). Specifically, perceived mastery-oriented motivational climate promoted autonomous motivation in PE, which in turn increased the five types of motivation in leisure-time PA and led to a higher stage of exercise behavior change. Conversely, perceived performance-oriented motivational climate reduced autonomous motivation in PE, which in turn decreased the five types of motivation in leisure-time PA and led to earlier stages of exercise behavior change. The patterns of the chain-mediating effects of autonomous motivation in PE and five types of motivation in leisure-time PA were somewhat similar in girls and boys. The results suggested that PE teachers should create learning-oriented climates and avoid performance-oriented motivational climates, which may promote students’ intrinsic or identified motivations for PA within and beyond PE classes and affect students’ leisure-time PA.